2011
DOI: 10.1007/s10163-011-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Solid waste management practices in Turkey

Abstract: As an economically developing country, Turkey has very well operated integrated solid waste management applications structured on modern facilities, besides over 2,000 scattered open dump areas in the country. Integrated waste management applications seem eligible for the metropolitan cities like Istanbul and Izmit (Kocaeli). Attempts have not been encouraging for the scattered regional settlements using central storage sites due to financial shortages and received rejections from nearby settlements. Small-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Attempts to use central storage sites have not been encouraging. Regional settlements are widely scattered, there are financial constraints and there are objections from nearby settlers [1]. Several studies have been conducted dealing with the generation and treatment of leachate [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to use central storage sites have not been encouraging. Regional settlements are widely scattered, there are financial constraints and there are objections from nearby settlers [1]. Several studies have been conducted dealing with the generation and treatment of leachate [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, every year the amount of waste and its consequent disposal problems increased due to the increase in the standards of living, industrialization, and thus population. Moreover, among 25 million tonnes, about 17.5 million tonnes was disposed without any control [2]. Hence, waste recycling is deemed as the most suitable solution because it decreases the pollution of the nature and also helps to reuse energy production procedure.…”
Section: Introductionmentioning
confidence: 99%
“…White et al (1995) added that, MSWs are difficult to manage as the components are diverse, with materials such as metal, paper, glass and other organics mixed together. Similarly, a study (Berkun et al, 2011) Dixon & Jones (2005) reported that, the compositions of municipal solid include materials such as soil, garden and food waste, wood, paper, ashes, plastics, textiles and rubber. They concluded that, municipal solid wastes are a collection of wastes that are mainly from household and commercial sources.…”
Section: Municipal Solid Waste (Msw)mentioning
confidence: 99%